Exploring the spatial effects and influencing factors of PM2.5 concentration in the Yangtze River Delta Urban Agglomerations of China. (1st January 2022) - He, Yong; Lin, Kunrong; Liao, Nuo; Chen, Zhihao; Rao, Jiwen
Abstract: The haze pollution caused by PM2.5 is a prominent environmental pollution issue in China, which seriously affects socioeconomic development and human health. However, previous studies ignored the heterogeneity among the different categories of cities in investigating the spatial effects of PM2.5 concentration and its influencing factors at the level of urban agglomerations. Therefore, this study takes 27 cities in the Yangtze River Delta Urban Agglomerations of China as a case study to identify the key influencing factors and their direct and spatial effects on PM2.5 in different categories of cities. The results indicate that a 1% increase in population density, energy intensity, industrial pollution emission, and public transport density causes the PM2.5 concentration to rise 0.264%, 0.088%, 0.021%, and 0.085%, respectively, in the whole urban agglomerations. In addition, a 1% increase in economic development and foreign direct investment decreases the PM2.5 concentration by 0.814% and 0.019%, respectively. In the first category, the main influencing factors of PM2.5 are population density, economic development, energy intensity, industrial pollution emission, and public transport density. In the second category, the main factors are economic development, energy intensity, and public transport density. In the third category, the major factors are industrial pollution emission, public transport density, and foreign direct investment. Moreover, population density, energy intensity, and public transport density have significant spatial spillover effects on PM2.5 in the first category. The population density, economic development, energy intensity, industrial pollution emission, and foreign direct investment have significant spatial spillover effects on PM2.5 in the second category. Population density and foreign direct investment have significant spatial spillover effects on PM2.5 concentration in the third category. Highlights: Spatial effect and driving factor of PM2.5 are explored at urban agglomeration level. The heterogeneity among different categories of cities in YRDUA is investigated. Both the spatial diffusion and time-lag characteristics of PM2.5 are considered. The driving factors of PM2.5 are examined through the dynamic spatial panel model. The spatial spillover effects of the factors on PM2.5 concentration are assessed.